The use of parabolic mirrors in combined low-coherence and confocal refractive index measurement - Francis, Daniel; Ford, Helen D.; Hallam, Jonathan M.; Tatam, Ralph P. (SPIE, 2019)
Low-coherence interferometry is combined with confocal scanning to provide remote refractive index and thickness measurements of transparent materials. The influence of lens aberrations in the confocal measurement is assessed through investigation of the axial point-spread functions (APSFs) generated using optical configurations comprised of paired aspherics and paired achromats. Off-axis parabolic mirrors are suggested as an alternative to lenses and are shown to exhibit much more symmetric APSFs provided the system numerical aperture is not too high. Refractive index and thickness measurements are made with each configuration with most mirror pairings offering better than twice the repeatability and accuracy of either lens pairing.
Keywords: confocal; low-coherence; interferometry; refractive index; parabolic mirror; aberration; point-spread function